Clinical Study of Posttraumatic Epilepsy - Myangaa, Amarjargal; Guntev, Tsagaankhuu; Avirmed, Tovuudorj (Central Asian Journal of Medical Sciences, 2015)
Objectives: To study the manifestations of the paroxysms, the variants of the course, and to determine the significant predictive factors for post-traumatic epilepsy (PTE) in Ulaanbaatar, Mongolia. Methods: We obtained the histories of 109 PTE patients who came to district health associations and the Central First Clinic in Ulaanbaatar from 2011 to 2013. We conducted a questionnaire and performed clinical examination to evaluate seizures in accordance with semiologic and international classification of epileptic seizures. Clinical data was matched with the results of electroencephalography (EEG), computed tomography (CT), and magnetic resonance imaging (MRI). Results: Of the 109 patients, 93 (85%) presented with secondary generalized partial seizure (SGPS), 16 (15%) with partial seizure and 66 (60.5%) with motor phenomena. The seizure frequency was not correlated with the structural brain abnormalities, but there was an inverse association (r=-0.32, p<0.001) between seizure frequency and the duration of PTE. PTE was positively correlated with severe injury, contusion, early onset of seizures (p><0.05), and operative brain injury (p><0.005). Conclusion: Clinical features of PTE were presented as secondary generalized seizure and motor phenomena in the majority of patients. PTE was characterized commonly by long durations of high seizure frequency and significantly affected by factors such as severity of head injury and operative brain injury.